High Prevalence of blaOXA-2 and blaOXA-10 Genes in the β-Lactam-Resistant Clinical Isolates of Pseudomonas aeruginosa - Fatemeh Bazari Jamkhaneh; Mina Owrang; Hamid Reza Goli (Research in Molecular Medicine)
Background: Increased resistance to β-lactams is one of the most important considerations about Pseudomonas aeruginosa. This study aimed to investigate the prevalence of blaOXA-2 and blaOXA-10 genes in β-lactam-resistant P. aeruginosa. Methods: In this study, 100 clinical isolates were collected, and β-lactam-resistant strains were identified using the disk agar diffusion test. Bacterial DNA was extracted by the sodium dodecyl sulfate method, and the polymerase chain reaction was used to identify blaOXA-2 and blaOXA-10 β-lactamase genes. Results: In total, 43 isolates were resistant to at least one of the β-lactams tested. Piperacillin-tazobactam and aztreonam were the most and least effective antibiotics, respectively. The resistance rate to a panel of β-lactams ranged from 12% to 37%. The highest rate of antibiotic resistance was related to wound and catheter specimens in burn and intensive care units. A significant relationship was observed between β-lactams resistance and the presence of blaOXA-2 and blaOXA-10 genes. Among 43 resistant isolates, 100% and 83.72% carried the blaOXA-2 and blaOXA-10 genes, respectively. Conclusion: High β-lactam resistance rates and prevalence of blaOXA-2 and blaOXA-10 in this study indicate these enzymes' significant role in resistance to β-lactams, possibly due to overuse of these antibiotics and their easier access.